Theoretical analysis of additional surrounding rock pressure in shallow buried bias tunnel - Tian Xiaoxu; Zhanping Song; Tong Wang; Jiangsheng Xie; Yun Cheng; Zhi Liu (Scientific Reports, 2024)
Abstract The existing calculation method for the surrounding rock pressure of shallow buried bias tunnel fails to account for the impact of the progressive failure characteristics of the surrounding rock and slope creep, thereby neglecting the additional pressure arising from slope creep. Therefore, the progressive instability failure mode of the surrounding rock of shallow buried bias tunnel was obtained by numerical simulation. Based on this, the theoretical analysis model of the additional pressure of shallow buried bias tunnel was established, and the calculation formula of the additional pressure was derived. Further analysis revealed that the larger the deformation rate of the surrounding rock, the shorter the time it takes for the additional pressure to reach its maximum value. When the deformation rate of surrounding rock increases to a certain value, there will be no additional pressure on the liner, that is, the pressure will be released when the surrounding rock is excavated. In such scenarios, if the strength of the first lining is inadequate, cracking or even collapse of the first lining may occur during excavation.